Aktivitas Antibakteri Rebusan Secang (Caesalpinia sappan L.) terhadap Salmonella thypii Secara In Vivo - Shirly Kumala; Devana Devana; Didik Tulus (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
One of the plant that has been used emperically for treatment was Caesalpinia sappan L“secang”. The bark of this plant contains metabolites with strong and effective antibaterial activity, namely tannin and brasilin. Two methods, namely A and B, were employed to perform the in vivo antibacterial study of this plant. In every method, there were six groups (K1-K6) which each of the group consisted of five mice. K1-K3 were the control groups consisting of control using healthy mice (K1), positive control in the presence of chloramphenicol (K2) and negative control (K3). The test groups were K4-K6, mice in these group were treated with different concentrations of “secang” water extract at 15%, 30% and 75%, respectively. The Salmonella thypii bacterial suspension was injected to the mice via intraperitonium adminsitration. In A method, treatment was given 2 hours after infecting the mice with the bacterial suspension, while in the B method, the treatment was given to the mice after 24 hours of bacterial infection. After 3 days of treatment, the intraperitonium fluid of the mice was taken under anaesthetic condition followed by qualitative and quantitative analysis of the biological sample obtained. Quantitative analysis via A method demonstrated that a decreased of 16.54%, 25.29 % and 25.12% in bacterial colony number was observed in the samples collected from K4, K5 and K6 respectively when compared to the respective controls. B method showed smalled decreased (3.37 %, 9.83 % and 20.48 %) in the colony number counted. The qualitative analysis demonstrated that the isolated bacterial strain was Salmonella typhi. In conclusion, boiled water extract of secang could act as effective antibacterial agent because it inhibit the growth of Salmonella thypii under in vivo study conditions.ABSTRAK Salah satu tanaman yang secara empiris banyak digunakan untuk pengobatan adalah Caesalpinia sappan L. (Secang). Batang dari tanaman secang mengandung tanin dan brasilin, yang berkhasiat sebagai antibakteri. Uji antibakteri rebusan secang dilakukan secara in vivo menggunakan 2 metode yaitu metode A dan metode B. Setiap metode terdiri dari 6 kelompok dan setiap kelompok terdiri dari 5 ekor mencit (mus musculus) putih jantan galur DDY. Masing-masing kelompok terdiri dari kontrol normal (K1), kontrol positif kloramfenikol (K2), kontrol negatif (K3) dan kelompok yang diberi rebusan secang konsentrasi 15 % (K4), 30 % (K5) dan 75 % (K6). Suspensi bakteri Salmonella thypii diinfeksikan ke mencit secara intraperitonium. Pada metode A, pengobatan diberikan 2 jam setelah mencit diinfeksi bakteri, sedangkan pada metode B, pengobatan diberikan 24 jam setelah mencit diinfeksi bakteri. Setelah tiga hari pengobatan, mencit dianestesi dan cairan intraperitonium mencit diambil untuk dilakukan uji kuantitatif dan uji kualitatif. Hasil uji kuantitatif metode A menunjukkan terjadi penurunan jumlah koloni bakteri dalam cairan intraperitonium mencit pada kelompok 4 (K4), 5 (K5) dan 6 (K6) terhadap kontrol negatif (K3) sebesar 16,54 %; 25,29 % dan 25,12 %; sedangkan pada metode B sebesar 3,37 %; 9,83 % dan 20,48 %. Hasil uji kualitatif pada metode A dan metode B menunjukkan bakteri yang terisolasi dari cairan intraperitonium mencit adalah Salmonella thypii. Hasil penelitian menunjukkan rebusan secang dapat menghambat pertumbuhan Salmonella thypii secara in vivo.